The State's liability regime in light of the standards set by the Galetovic Sapunar and Others v. Chile ruling. An analysis of the Chilean situation - Farfán Saldaña, Gustavo (2025)
This article aims to analyze the effects of the recent Galetovic Sapunar et al. v. Chile judgment by the Inter-American Court of Human Rights, particularly regarding the statute of limitations for indemnity actions arising from human rights violations that do not constitute crimes against humanity or are not considered serious human rights violations but are nonetheless attributable to the State. To this end, the article first examines the Galetovic Sapunar judgment and the standards established by the Court. Secondly, it reviews the prevailing approach in Chile concerning indemnity actions against the administration, with a particular focus on the rules governing extinctive prescription. Based on these two aspects, the article analyzes the necessary changes to ensure compliance with the judgment and align the domestic legal framework with the standard set by the Inter-American Court of Human Rights.